2020
DOI: 10.3390/v12060599
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Epidemic Diarrhea Virus nsp15 Antagonizes Interferon Signaling by RNA Degradation of TBK1 and IRF3

Abstract: Porcine epidemic diarrhea virus (PEDV) causes a porcine disease associated with swine epidemic diarrhea. The type I interferon (IFN-I or IFN α/β) is a key mediator of innate antiviral response during virus infection. Different antagonistic strategies have been identified and determined as to how PEDV infection inhibits the host’s IFN responses to escape the host innate immune pathway, but the pathogenic mechanisms of PEDV infection are not fully elucidated. Our preliminary results revealed that endogenous TANK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…The nsp15-defective MHV exhibits severe replication defects in macrophages and is highly attenuated in mice [51,52]. In addition to MHV [51,52,65], the nsp15s from PEDV, SARS-CoV-2, SARS-CoV, and HCoV-229E are also characterized to be IFN antagonists [51,53,[71][72][73]. By using a transcriptomics approaches to evaluate the host transcriptional response, Volk demonstrated that MHV nsp15 substantially contributes to the ability of coronaviruses to evade the host innate response in macrophages [65].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The nsp15-defective MHV exhibits severe replication defects in macrophages and is highly attenuated in mice [51,52]. In addition to MHV [51,52,65], the nsp15s from PEDV, SARS-CoV-2, SARS-CoV, and HCoV-229E are also characterized to be IFN antagonists [51,53,[71][72][73]. By using a transcriptomics approaches to evaluate the host transcriptional response, Volk demonstrated that MHV nsp15 substantially contributes to the ability of coronaviruses to evade the host innate response in macrophages [65].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Enzymatic activity occurs in the C-terminal EndoU domain, which is more broadly conserved across nidoviruses, suggesting that this endoribonuclease activity is critically important for large, positivestrand RNA viruses (5,6). Work in animals and cell culture has shown that Nsp15 function is not necessary for viral replication, however Nsp15 nuclease activity is critically important for evasion of the host immune response to the virus, specifically by preventing the activation of dsRNA sensors (7)(8)(9)(10)(11). For example, in studies of porcine endemic diarrhea virus (PEDV), Nsp15-deficient virus resulted in higher levels of type I and III interferon responses in cells, and piglets infected with the mutant virus had much higher survival rates than those infected with WT PEDV (8).…”
Section: Introductionmentioning
confidence: 99%
“… [ 188 ] Nsp7, nsp8 and nsp9 Inhibits the IFN-β and IRF3 promoter activities, viral replication [ 67 , 68 , 129 ] Nsp13-16 Involves in viral replication; inhibition of the type I IFN and the type III IFN; vital virulence factors. [ 80 , 84 , 85 , 129 , 189 , 190 ] Structural proteins S Induces neutralizing antibodies; receptor binding and membrane fusion; a vital virulence factor; S1 Spike protein induces cell apoptosis. [ 119 , 191 , 192 ] E Stimulates ER stress and up-regulates the production of IL-6 and IL-8; promotes apoptosis; inhibits the IFN promoter activities.…”
Section: Pedv Genome Structure and Functionsmentioning
confidence: 99%
“…PEDV nsp15 was could subvert the IFN response by the RNA degradation of TBK1 and IRF3 in HEK293T and IPEC-J2 cells. H226, H241 and K282 of PEDV nsp15 were crucial for the EndoU activity [ 84 ]. H226A, H241A and K282A in nsp15 probably provide a universal approach for generating live-attenuated vaccine candidates for emerging coronaviruses [ 85 ].…”
Section: Pedv Genome Structure and Functionsmentioning
confidence: 99%